Subwavelength elastic topological negative refraction in ternary locally resonant phononic crystals. (15th May 2021) - Huang, Hongbo; Huo, Shaoyong; Chen, Jiujiu
Highlights: Defect-immune topological negative refraction of elastic waves in ternary phononic crystals is realized at the deep subwavelength scale. Elastic valley polarized edge modes induced by locally resonant state are obtained. Total wave mode conversion from longitudinal waves to transverse waves is revealed. A topological elastic valley filter is designed by utilizing the valley-selective excitation. Graphical abstract: Image, graphical abstract Abstract: Negative refraction of elastic waves has attracted significant research interest due to its potential prospects in acoustic imaging, communication, and structural health monitoring. However, previous implementations based on Bragg interference suffer from lattice-scale size restrictions or defect-sensitive characteristics, hindering their application in compact subwavelength systems. Here, we propose a new design of ternary valley-Hall phononic crystals (PCs) with subwavelength topological negative refraction. By introducing the subwavelength resonators into a complex lattice similar to graphene allotrope, the valley polarized edge modes induced by locally resonant state are obtained, and the defect-immune topological negative refraction of the edge states outcoupling into free space is established. Furthermore, the total mode conversion from longitudinal to transverse waves is demonstrated by the wave mode separation and the equifrequency curves (EFCs) analysis on the negative refraction. Finally, utilizing the valley-selective excitation, a topological elastic valley filter is designed by coupling the valley-projected edge states with bulk valley polarizations. The research provides new possibilities for robust control of isolated transverse elastic waves in the deep subwavelength regime that can be employed for designing compact communication devices.